Malic enzyme 2 and susceptibility to psychosis and mania - Dae Lee, Byung (2007)
Previous studies have identified a putative gene locus for both schizophrenia and bipolar disorder in the chromosome 18q21 region. To identify candidate genes associated with these disorders we completed fine mapping analyses (using microsatellite markers) in 152 families from the Central Valley of Costa Rica (CVCR) (376 total subjects, 151 with a history of psychosis, 97 with a history of mania). Microsatellite analyses showed evidence of association at two contiguous markers, both located at the same genetic distance and spanning approximately 11 known genes. In a corollary gene expression study, one of these genes, malic enzyme 2 (ME2), showed levels of gene expression 5.6-fold lower in anterior cingulate tissue from post-mortem bipolar brains. Subsequent analysis of individual SNPs in strong linkage disequilibrium with the ME2 gene revealed one SNP and one haplotype associated with the phenotype of psychosis in the CVCR sample. ME2 interacts directly with the malate shuttle system, which has been shown to be altered in schizophrenia and bipolar disorder, and has roles in neuronal synthesis of glutamate and gamma-amino butyric acid. The present study suggests that genetic variation in or near the ME2 gene is associated with both psychotic and manic disorders, including schizophrenia and bipolar disorder.